2009
DOI: 10.1063/1.3103268
|View full text |Cite
|
Sign up to set email alerts
|

Accurate ab initio double many-body expansion potential energy surface for ground-state H2S by extrapolation to the complete basis set limit

Abstract: A single-sheeted potential energy surface is reported for the electronic ground-state of H(2)S by fitting accurate multireference configuration interaction energies calculated using aug-cc-pVTZ and aug-cc-pVQZ basis sets with extrapolation of the electron correlation energy to the complete basis set limit, plus extrapolation to the complete basis set limit of the complete-active-space self-consistent field energy. A switching function formalism has been used to warrant the correct behavior at the H(2)(X (1)Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 61 publications
7
61
0
5
Order By: Relevance
“…Given the high level of ab initio calculations used in its construction, one can expect a higher degree of accuracy as compared with previous PESs for the ground 1 1 A state of the SH 2 system. The few dynamical studies available on this PES at the time 30 pointed at different dynamical effects to those calculated on the RKHS PES (Ref. 14) and even with those reported for a similar PES by the same authors 30,32 to be addressed further below.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Given the high level of ab initio calculations used in its construction, one can expect a higher degree of accuracy as compared with previous PESs for the ground 1 1 A state of the SH 2 system. The few dynamical studies available on this PES at the time 30 pointed at different dynamical effects to those calculated on the RKHS PES (Ref. 14) and even with those reported for a similar PES by the same authors 30,32 to be addressed further below.…”
Section: Introductionmentioning
confidence: 82%
“…The few dynamical studies available on this PES at the time 30 pointed at different dynamical effects to those calculated on the RKHS PES (Ref. 14) and even with those reported for a similar PES by the same authors 30,32 to be addressed further below. In particular, the values of their QCT thermal rate constants at 300 K for different isotopes and intramolecular and intermolecular kinetic isotope effects were presented in Ref.…”
Section: Introductionmentioning
confidence: 82%
“…Had we determined the CRPs on the DMBE/CBS PES, 46 we would have found noteworthy differences with the results obtained on the RKHS and DMBE/SEC PES. This is due to the fit resulting in DMBE/CBS PES that produced some artifacts which amounts to a barrier at compressed H-H internuclear distances.…”
Section: A Cumulative Reaction Probability For J =mentioning
confidence: 58%
“…28,42 It has been also found that, at least at low energies, the reaction takes place mostly via an insertion mechanism involving a long-lived complex. Recent experiments at very low collision energies performed by Costes co-workers 43 and Sims and co-workers 44 as well as the new set of PESs calculated by Song et al, 46,47 as an alternative to the widely used reduced-kernel Hilbert space (RKHS) PES by Ho et al, 30 have attracted a renewed interest on this system. In this paper, we will apply the methodology inherent to the CRP formalism to the S( 1 D) + H 2 reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In order to carry out the extrapolation, electronic energy in the MRCI(Q) calculation is expressed by a sum of two terms [45,51] ,…”
Section: Extrapolation To the Cbs Limitmentioning
confidence: 99%